The effect of divertor closure on the impurity stagnation point in detached L-mode discharges on DIII-D - M.G. Burke; F. Scotti; S.L. Allen; W.H. Meyer; A. Holm; M. Zhao; A.G. McLean; M. Fenstermacher; H.Q. Wang; R. Wilcox (Nuclear Materials and Energy)
This paper presents experimental measurements of the location of the impurity flow stagnation point in the scrape-off-layer (SOL) of a tokamak plasma. Coherence imaging of carbon-2+ emission (465 nm) is used to track the main-chamber impurity velocity of DIII-D L-mode plasmas with B×∇B out of the divertor. The C2+ flow stagnates near the top or crown of the plasma when an open divertor (no baffling) is used. In contrast, with matched conditions and using a divertor with baffling, the C2+ flow stagnates near the outer divertor leg (X-point). The C2+ poloidal emission is hollow, peaking near the divertor legs, in the open configuration. In contrast, in the closed configuration, the C2+ emission is flat through most of the main-chamber SOL. Changing divertor dissipation from attached to detached conditions had only a minor effect on the main-chamber midplane impurity velocity. Numerical simulations using the multi-fluid edge transport code UEDGE including cross-field drifts show qualitative agreement with the open divertor experimental result.